Are there contractual remedies to obtain compensation for moral damage arising from breach of contract? - Yzquierdo Tolsada, Mariano (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The convenience of there being in the general regime of contract law an express recognition of the moral damage followed from a breach of contract is raised. When damage occurs as a consequence of the breach of an obligation stipulated in the contract, or at least has its place in the obligations that, although nothing has been expressly said in the contract, are also part of it, there should be no need to escape of the contractual orbit to find the answer through law of torts means. A contract requires compliance with what is expressly agreed, but also all consequences that, according to their nature, are in accordance with good faith, custom and law. Such moral damage will only be non contractual if it is not possible to place it in the sphere of the goods that were taken into account when entering into the contract or should have been taken into account.
Keywords: Fault; moral damage; contractual liability